The The Effect of Simplicia Drying Method on the Acquisition of Active Compound Levels of Grinting Grass Simplicia Extract (Cynodon dactylon (L.) Pers.) - Yasi, Ratna Mustika; Harsanti, Restiani Sih; Larasati, Tiara Trisna (BERKALA SAINSTEK, 2022)
The drying method is the most important step in maintaining levels active compound in the sample. This study aims to determine the effect drying method against levels of active compounds of grinting grass (Cynodon dactylon (L.) Pers.). Drying methods include sun drying and cabinet drayer. The results showed that the drying method in plants reduced the extractive gain from the levels of active compounds including flavonoids, polyphenols, steroids, terpenoids, alkaloids and saonins. Simplicia drying method gave a significant effect (p<0.05) on the extraction of the active compound content of grinting grass (Cynodon dactylon (L.) Pers.). Based on the two drying methods, the highest levels of active compound extractive were obtained in the cabinet drayer method compared to the drying method using sunlight.